Self-pollination in the genus Erica - Malan, Michelle (Department of Biological Sciences, 2017)
The ability of flowers to self-pollinate was investigated in eight species of the diverse Erica genus. Self-pollination was found to occur in five out of the eight species, with mainly bird pollinated species having a high degree of selfing. The use of a broken anther ring as an indication of visitation and pollination of the flowers was also investigated and it was found that two species are potentially useful in this regard. An inverse relationship between the degree of selfing and near neighbour distance was found across the species. The resprouting Erica cerinthoides was found to have a UV signal, it also had the most dispersed population, highest nectar sugar concentration and a high degree of self-pollination. Erica paludicola, which is an endemic that occurs in only one other population on the Cape Peninsula, had the highest degree of self-pollination. I speculate that the high degree of selfing in Erica is one of the reasons the genus is so diverse, and that the ability to self will preserve this diversity in the face of increasing habitat destruction and fragmentation, at least temporarily.